A comparison of cyst age and assay method of the efficacy of contact lens disinfectants againstAcanthamoeba. Issue 3 (1st March 2001) - Kilvington, Simon; Anger, Claude
Abstract : AIMS: (i) To determine effect of Acanthamoeba cyst age, method of production, and (ii) to assay technique on the efficacy of multipurpose solutions (MPS) and hydrogen peroxide based contact lens disinfectants. (iii) To establish if MPS can remove mature cysts from contact lenses according to the ISO/DIS 14729 regimen test for microbe removal. METHODS: Immature and mature cysts of A polyphaga were tested against the MPS Opti-Free express and the hydrogen peroxide based solutions Oxysept 1Step and Oxysept 1 using two assay methods. Simulated patient regimen testing was performed with the Opti-Free express and Complete using mature cysts inoculated on to group I or group IV lenses. RESULTS: Immature cysts were sensitive to disinfection by all solutions. No killing was observed with mature cysts with Opti-Free express, while immature cysts yielded a 1–2 log reduction in viability. Oxysept 1Step gave a 1.1 (SD 0.3) log reduction in mature cysts after 6 hours. Oxysept 1 gave a 2.4 (0.3) log reduction in mature cysts after 4 hours and a 3.8 (0.5) log reduction after 6 hours. Patient regimen testing using Opti-Free express and Complete resulted in no recovery of viable mature cysts from the contact lenses or from the soaking solutions. CONCLUSION: Cyst age but not method of production used in this study influences the efficacy of contact lens disinfectants against Acanthamoeba . MPS are effective in removing cysts from contact lens surfaces and may have a role in the prevention of acanthamoeba keratitis.